The effect of antimycin A on the intensity of oxidative stress, the level of lipid peroxidation and antioxidant enzyme activities in different organs of wheat (Triticum aestivum L.) seedlings subjected to high temperature - Batjuka, Anna; Škute, Natalja (Archives of Biological Sciences, 2017)
The objective of the present investigation was to identify the effect of antimycin A (AA) as an activator of the alternative pathway (AP) of respiration, on oxidative stress intensity, the level of lipid peroxidation (LPO) and activities of H2O2 scavenging enzymes in functionally different organs of Triticum aestivum L. subjected to short- and long-term exposure to high temperature (HT). The level of LPO was assessed in terms of malondialdehyde (MDA), an indicator of oxidative injury. The results demonstrated increases in the total content of reactive oxygen species (ROS) and MDA production in developing and senescent organs of wheat seedlings, and significant augmentation of the activities of the antioxidant enzymes, catalase and ascorbate peroxidase, in different organs in response to exposure to HT. The activation of the AP by AA restrained ROS production in the mitochondrial electron transport chain (mETC) under exposure to HT. https://doi.org/10.2298/ABS160706134B Received: July 6, 2016; Revised: October 31, 2016; Accepted: November 30, 2016; Published online: December 15, 2016 How to cite this article: Batjuka A, Škute N. The effect of antimycin A on the intensity of oxidative stress, the level of lipid peroxidation and antioxidant enzyme activities in different organs of wheat (Triticum aestivum L.) seedlings subjected to high temperature. Arch Biol Sci. 2017;69(4):743-52.